Comunicación externa para el fortalecimiento de la imagen institucional de la empresa de suministros Florícolas Mallatec, ciudad de Quito, período mayo-agosto del 2022. - García Caiza, Anahí Jamilex (2023)
External communication and institutional image are two of the main tools that any company should use in order to improve its communication development and its brand positioning. Mallatec is a floral supplies producer located in Conocoto, Quito, Ecuador. This is a company committed to good service and quality, Nevertheless, many people do not know about all the services they offered to floral businesses due to the lack of advertising and social media strategies. This research pretends to help this company to face their problems in a better way. This project applies a qualitative study through interviews, focus groups and observation sheets. These research instruments determined the importance of the creation of an external communication plan, in order to strengthen the institutional image of Mallatec. Key words: external communication, institutional image, strengtheness, external communication plan, floral supplies.